2004
DOI: 10.1002/jqs.862
|View full text |Cite
|
Sign up to set email alerts
|

Iberian Plio‐Pleistocene biochronology: micromammalian evidence for MNs and ELMAs calibration in southwestern Europe

Abstract: A multivariate biochronological analysis of the Plio-Pleistocene Iberian rodent fossil record is presented. Among more than 300 fossil sites, 49 sites have been selected. The ordination of the fossil sites selected from the Iberian Peninsula has been achieved by the appearance event ordination method. After calibration of this ordination with geochronological dates at some of the localities, numerical dates are proposed for all the localities studied. Hence, mammal fossil sites non-datable by other means (pala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…In this work we used the faunal lists of rodent communities from 44 fossil sites from the Iberian Plio-Pleistocene (Table 1) dated between 5.25 and 0.01 Ma [38]. These fossil sites have been subject to intensive sampling during the last fifty years (see references in [38]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we used the faunal lists of rodent communities from 44 fossil sites from the Iberian Plio-Pleistocene (Table 1) dated between 5.25 and 0.01 Ma [38]. These fossil sites have been subject to intensive sampling during the last fifty years (see references in [38]).…”
Section: Methodsmentioning
confidence: 99%
“…These fossil sites have been subject to intensive sampling during the last fifty years (see references in [38]). The minimum sample required to include a fossil site in our study was 100 first and second upper and lower molars, which is considered the minimum number necessary to render a representative sample of the original paleocommunity [30,36,39].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis does not consider species exclusive to one locality, known as singletons. A new version named Appearance Event Ordination (AEO; Alroy, 1994) makes it possible to include available information on stratigraphic superposition between fossil localities (Wing et al, 1995;Hernandez Fernandez et al, 2004;Hammer and Harper, 2006). This software calculates for each faunal list the First Appearance Event (FAE) of one species with regard to the Last Appearance Event (lAE) of another.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have suggested the inclusion of some additional fossil sites in the analysis to avoid mathematical anomalies, which affect the boundaries of the temporal distribution studied Hernandez Fernandez et al, 2004;Domingo et al, 2007). Therefore, in order to polarize the upper end of the sequence, we included some fossil sites from MN 14 (Caravaca 1, Celadas 9, Gorafe 1, La Gloria 4, Peralejos E and Purcal 4 for the southern province; Celleneuve, Font Estramar, Hautimagne and Vendargues for the northern province), which are younger than the study interval being analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation